Il futuro è già qui - Viale, Guido (Scienze del Territorio, 2020)
Despite the authoritative warnings (from IPCC to COP 21, from Pope Francis to Greta Thunberg) climate crisis is reaching irreversibility. Besides essential mitigation measures (stopping as soon as possible extraction and use of fossils, useless and harmful Major Projects, relocations to save on environmental and labour costs, and analogous) adaptation measures must be put in place as soon as possible to face life conditions becoming more and more difficult. International institutions and governments have not been up to the task, therefore local communities must lead the turn, recreating inside themselves and in their mutual relations conditions that promote a wider autonomy both in managing their own territories and in the production field through the reterritorialisation of many activities now spread throughout the planet. Efficiency and energy generation from local and differentiated renewable sources; ecological, proximity and multifunctional agriculture and farming for a healthy and sustainable diet; ecodesign finalized to zero waste; drastic reduction of mobility based on private motorization and care of hydrogeological systems. These are the core intervention fields for the unavoidable ecological conversion: a process requiring a strong popular participation, but also an inevitable conflict with the established powers.